Towards the development of photoresponsive molecular assemblies - Cunningham, M (2016)
The emergence of complex, carefully designed, molecular architectures incorporating either a lanthanide ion or the porphyrinic macrocycle have stimulated significant interest of late, particularly in the fields of molecular switches, molecular machines and data storage systems. The integration of these emissive species has been shown to permit the analysis of conformational, coordinative, or electronic change, and employed, in the case of the porphyrinic macrocycle, to acquire a deeper understanding of the natural process of photosynthesis, thus opening up the possibility of developing more efficient and inexpensive photovoltaic cells. This thesis begins by providing insight into the generation of cathodic photocurrent density within both monophasic and biphasic self-assembled monolayers, before documenting how the magnitude of such photoelectochemical output can be gated upon the integration of an electron relay moiety, both at the interface and into solution. The introduction of an electron relay moiety into solution has been shown to bring about increases of up to 283 % in the magnitude of the cathodic photocurrent density acquired, whilst optimisation of the distances between the metallic interface, the electron relay moiety and the porphyrinic macrocycle has also proven beneficial. Greatest photoelectrochemical output (5.1 x 1014 nA mol-1 cm-2) is realised when the porphyrinic macrocycle is covalently tethered at a distance of 4.6 nm from the quenching, metallic interface, and the relay moiety integrated at a distance of 1.7 nm from the interface and 2.9 nm from the porphyrinic macrocycle, respectively. However, greatest variation (94 %) in the magnitude of the cathodic photocurrent densities acquired is observed when the distance between the porphyrinic macrocycle and the gold surface is kept at 3.3 nm, and the relay moiety situated at either 1.2 nm or 1.7 nm from the interface, respectively. Research then moved towards trying to integrate this established conformational ruler within a porphyrin-appended, bistable [2]rotaxane. Its implementation served to try to ensure that photoelectrochemical differentiation of the ground state coconformation (GSCC) and the metastable state co-conformations (MSCC) was viable, thus enabling the efficient resolution of anion-induced molecular motion within a dynamic supramolecular architecture by means of a novel approach. The focus of this thesis then shifts to the assembly of novel, optically switchable, ternary complexes exhibiting charge-transfer based on the donor-acceptor interaction between an electron-rich naphthalene derivative (EuNap) and MV2+, an electron-poor, redox-addressable moiety. Prior to the deposition of (MV, EuNap)-CB[8] at the interface, the homoternary analogue ((MV+.)2-CB[8]) was acquired upon one electron reduction of (MV, EuNap)-CB[8] in the presence of excess MV2+. This process was revealed to be reversible upon the application of a stream of oxygen, and the relative concentration of each complex present in solution quantified upon mathematical manipulation of the biexponential decay curve acquired; upon the addition of sodium thiosulfate (Na2S2O3), the percentage of uncomplexed EuNap (τ = 0.60 ms cf. τ = 0.1 ms (MV, EuNap)-CB[8]) present in solution increased in accordance with the generation of ((MV+.)2-CB[8]) and loss of the charge-transfer interaction (λmax = 390, 490 nm), of which has been shown to quench lanthanide luminescence (Eu3+, Yb3+, Nd3+). Thus, the assembly of a molecular switch is documented which may be followed qualitatively at higher concentration by a visible colour change, and at low concentrations quantitatively by virtue of luminescence spectroscopy. No optical output (λex = 227 nm, λem = 616 nm) was acquired upon the deposition of (MV, EuNap)CB[8]) due to the occurrence of surface energy transfer (SET). As a result, 1-(10-mercaptodecyl)-1'methyl-[4,4'-bipyridine]-diium bromide and 1-methyl-1'-(10-(naphthalen-2yloxy)decyl)-[4,4'bipyridine]-1,1'-diium bromide iodide were synthesised and the assembly of a molecular film envisaged in which the molecular recognition properties of CB[n] were maintained and significant optical output from the lanthanide ion (Eu3+, λem 616 nm) detected; the assembly of such a film centred on the formation of 1:2 intermolecular heteroternary complexes and the recruitment of EuNap at a distance ≥ 3.2 nm from the gold substrate. It was envisaged that the modulation of any emissive output would be brought about upon manipulating the oxidation state of a surface-confined metallocene. This thesis ends by summarising the research conducted and assessing how the inclusion chemistry of cucurbit[8]uril and the photophysical properties of the porphyrinic macrocycle can be combined in order to fabricate a dynamic, photoresponsive molecular assembly. The electrical energy generated from the efficient harvesting of light energy could be used in a multitude of applications, most notably as a nanoscale power supply to drive and control molecular and supramolecular actuations.